Ecotoxicology of polycyclic aromatic hydrocarbons and petroleum wastewater in the orinoquia region (2023)
Polycyclic aromatic hydrocarbons (PAH) are ubiquitous and characterized by low solubility, persistence in the environment, bioaccumulation in biota and high toxicity. Aquatic systems receive PAH through atmospheric deposition and direct runoff release, with the organisms that inhabit them being their main targets. Among these, ﬁsh are of particular interest because they occupy key positions in aquatic and terrestrial food webs. Petroleum extraction is one of the most relevant sectors in Colombia's economy; however, the environmental impact due to oil extraction and spillage accidents has generated contamination of soils and water sources, mortality of fauna and ﬂora or changes in the dynamics of natural ecosystems, among others. Biomonitoring of oil pollution using aquatic organisms, especially native species has a great ecological relevance. In this sense, ﬁsh are considered as one of the main sentinel species to assess the state of aquatic ecosystems because they are ubiquitous in most aquatic environments exposed to contaminants and also because of their ecological relevance. Our data show alterations in ﬁsh from oil industry wastewater discharge sites and ﬁsh exposed to different PAH. In fact, concentrations of 250 and 70 ng/L of naphthalene (NAP) and phenanthrene (PHE), respectively, were recorded in rivers exposed to the discharge of produced water. Subacute exposures to sublethal concentrations of NAP 100 µg/g, PHE 50 µg/g and benzo[a]pyrene (BaP) 10 µg/g were evaluated. The results shown presence of genotoxicity in peripheral blood erythrocytes and nuclear abnormalities being higher in ﬁsh exposed to PHE, followed by BaP, and NAP, alteration in antioxidant response, ﬁsh exposed to BaP showed a signiﬁcant increase in 7ethoxyresoruﬁn-O-deethylase activity compared to the control, and presence of deleterious changes in tissue architecture such as hyperemia, degeneration of the nuclei, cytoplasmic degeneration, and vacuolization that could lead in the long term to a decline in ﬁsh populations exposed to these conditions. In conclusion, the results show that native Colombian ﬁsh such as Aequidens metae, Astyanax gr. bimaculatus and Piaractus orinoquencis are good sentinels of freshwaters potentially contaminated by hydrocarbons or in laboratory studies aimed at understanding the impact of petroleum compounds. Acknowledgment: This study was funded by Colciencias-ANH and Universidad de los Llanos Project number 112272151869, grant 721 – 2015.